Histopathological Features and Protein Markers of Arrhythmogenic Cardiomyopathy - Bueno-Beti, Carlos; Asimaki, Angeliki (Frontiers in Cardiovascular Medicine, 2021)
Arrhythmogenic cardiomyopathy (ACM) is a heritable heart muscle disease characterized by syncope, palpitations, ventricular arrhythmias and sudden cardiac death (SCD) especially in young individuals. It is estimated to affect 1:5,000 individuals in the general population, with >60% of patients bearing one or more mutations in genes coding for desmosomal proteins. Desmosomes are intercellular adhesion junctions, which in cardiac myocytes reside within the intercalated disks (IDs), the areas of mechanical and electrical cell-cell coupling. Histologically, ACM is characterized by fibrofatty replacement of cardiac myocytes predominantly in the right ventricular free wall though left ventricular and biventricular forms have also been described. The disease is characterized by age-related progression, vast phenotypic manifestation and incomplete penetrance, making proband diagnosis and risk stratification of family members particularly challenging. Key protein redistribution at the IDs may represent a specific diagnostic marker but its applicability is still limited by the need for a myocardial sample. Specific markers of ACM in surrogate tissues, such as the blood and the buccal epithelium, may represent a non-invasive, safe and inexpensive alternative for diagnosis and cascade screening. In this review, we shall cover the most relevant biomarkers so far reported and discuss their potential impact on the diagnosis, prognosis and management of ACM.